Implementación de la metodología 5 "s" en almacén de repuestos automotrices - Garcia Ochoa, Erasmo (2013)
This article describes the implementation of the methodology 5 "S" (Seiri: Classification), (Seiton: Order), (Seiso: Clean), (Seiketsu: Standardization), (Shitsuke: Maintaining discipline) in an auto parts store milagro city - Ecuador, which was made an initial diagnosis of the store, throwing the problem of not finding the spare parts easily, then analyzed the main causes of quality problems using tools such as: Pareto diagrams, diagram cause-effect and process flow diagram. Inside the implementation of the methodology 5 "S" can be displayed at each step the actions taken to implement it in an effective way, in this way we proceeded to order each part according to the output stream with each thus obtained the result that the parts in the warehouse are organized, and so they can be easily placed keeping the place clean, and checklists were created to observe deviations that lead us to the initial disorder. As an added bonus you create a form in Excel with the help of Microsoft Visual Basic. This form makes the billing process digitally automatically discounting products sold inventory offering better control of the stock of spare parts.